Fast and reversible crosslinking of a silk elastin-like polymer. (15th March 2022) - Gonzalez-Obeso, Constancio; Rodriguez-Cabello, J.C.; Kaplan, David L.
Abstract: Elastin-like polymers (ELPs) and their chimeric subfamily the silk elastin-like polymers (SELPs) exhibit a lower critical solvation temperature (LCST) behavior in water which has been extensively studied from theoretical, computational and experimental perspectives. The inclusion of silk domains in the backbone of the ELPs effects the molecular dynamics of the elastin-like domains in response to increased temperature above its transition temperature and confers gelation ability. This response has been studied in terms of initial and long-term changes in structures, however, intermediate transition states have been less investigated. Moreover, little is known about the effects of reversible hydration on the elastin versus silk domains in the physical crosslinks. We used spectroscopic techniques to analyze initial, intermediate and long-term states of the crosslinks in SELPs. A combination of thermoanalytical and rheological measurements demonstrated that the fast reversible rehydration of the elastin motifs adjacent to the relatively small silk domains was capable of breaking the silk physical crosslinks. This feature can be exploited to tailor the dynamics of these types of crosslinks in SELPs. Statement of significance: The combination of silk and elastin in a single molecule results in synergy via their interactions to impact the protein polymer properties. The ability of the silk domains to crosslink affects the thermoresponsive properties of the elastin domains. These interactions have been studied at early and late states of the physical crosslinking, while the intermediate states were the focus of the present study to understand the reversible phase-transitions of the elastin domains over the silk physical crosslinking. The thermoresponsive properties of the elastin domains at the initial, intermediate and late states of silk crosslinking were characterized to demonstrate that reversible hydration of the elastin domains influenced the reversibility of the silk crosslinks. Graphical abstract: Image, graphical abstract